Marx dictionary - Fraser, Ian, 1962- (Continuum philosophy dictionaries., 2011)
The Marx Dictionary is a comprehensive and accessible guide to the world of Karl Marx. Meticulously researched and extensively cross-referenced, this unique book covers all his major works, ideas and influences and provides a firm grounding in the central themes of Marx's thought from a philosophical perspective. Students will discover a wealth of useful information, analysis and criticism. A-Z entries include clear definitions of all the key terms used in Marx's writings, coverage of their German origins, and detailed synopses of all his key works. The Dictionary also includes entries on Marx's major philosophical and political influences and contemporaries.